Proportional Changes in Cognitive Subdomains During Normal Brain Aging - Statsenko, Yauhen; Habuza, Tetiana; Gorkom, Klaus Neidl-Van; Zaki, Nazar; Almansoori, Taleb M.; Al Zahmi, Fatmah; Ljubisavljevic, Milos R.; Belghali, Maroua (Frontiers in Aging Neuroscience, 2021)
Background: Neuroscience lacks a reliable method of screening the early stages of dementia. Objective: To improve the diagnostics of age-related cognitive functions by developing insight into the proportionality of age-related changes in cognitive subdomains. Materials and methods: We composed a battery of psychophysiological tests and collected an open-access POBA dataset by testing individuals without dementia. To extend the utility of machine learning classification in cognitive studies, we proposed estimates of the disproportional changes in cognitive functions: index of simple reaction time to decision-making time (ISD), ISD with the accuracy performance (ISDA), index of performance in simple and complex visual-motor reaction with account for accuracy (ISCA). Studying the distribution of the values of the indices over the age allowed us to verify whether diverse cognitive functions decline equally throughout life or there is a divergence in age-related cognitive changes. Results: Unsupervised ML clustering shows that the optimal number of homogeneous age groups is four. The sample is segregated into the following age groups: Adolescents [0, 20), Young adults [20, 40), Midlife adults [40, 60) and Older adults 60 year of age. For ISD, ISDA and ISCA values only the median of the Adolescents group is different from that of the other three age groups sharing a similar distribution pattern (P > .01). After neurodevelopment and maturation, the indices preserve almost constant values with a slight trend towards functional decline. The RMO test results (RMO_mean) follow another tendency. The Midlife adults group’s median significantly differs from the remaining three age subsamples (P < .01). No general trend in age-related changes of this dependent variable is observed. For all the data (ISD, ISDA, ISCA, and RMO_mean) Levene’s test reveals no significant changes of the variances in age groups (P > .05). Homoscedasticity also supports our assumption about stable linear dependency between observed features and age. Conclusion: In healthy brain aging, there are proportional age-related changes in the time estimates of information processing speed and inhibitory control in task switching. Future studies should test patients with dementia to determine whether the changes of the aforementioned indicators follow different patterns.